Pengaruh Moderasi Karakteristik Komite Audit Dengan Opini Audit Going Concern Pada Pergantian Auditor - Merawati, Luh Komang; Badera, I Dewa Nyoman; Suardikha, I Made Sadha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume.02.No.09.Tahun 2013, 2013)
Modified going-concern audit opinion is expressed when the auditor found doubts about the entity’s sustainability. Issuance of going-concern audit opinion is not expected by the entity. Audit committee as corporate governance mechanisms are believed able to minimize the tendency of auditor change after the issuance of going-concern audit opinion. Hypothesis testing is divided into two logistic regression models using simple linear regression and MRA. The research results: 1) going concern audit opinion affects significantly on the possibility of auditor changes with the negative direction. 2) the influence of moderating audit committee’s characteristics such independence as well as accounting and financial expertise is significant and reinforces the negative effects of going concern audit opinion on auditor changes, while governance expertise and activity hold insignificant influence. Keywords: going concern, audit committees, corporate governance, auditors change